Policies, practices and outcomes of demand oriented community water supply in Ghana: The National Community Water and Sanitation Programme 1994 - 2004 - Veronika Fuest (University of Bonn, Center for Development Research (ZEF), 2005)
This study deals with the implications of policies of the so-called demand-driven approach of community water supply in rural and small urban areas in Ghana. In the context of comprehensive reforms in the water sector a transition of roles and responsibilities as well as the establishment of new institutions and actors were supported by numerous international donor organisations. Reorienting the water sector policies resulted, among others, in the National Community Water and Sanitation Programme (NCWSP), which started to operate in 1994. The policies directed at sustainable drinking water supply were to ensure community ownership and sustainability of facilities by beneficiary capital cost contributions, private sector participation, and cost-recovery water tariffs. After ten years of programme implementation a multilevel analysis of interrelationships between institutions, policy instruments and actors point to a variety of inconsistencies in programme planning and implementation which put the long-term sustainability of water supply at stake. Capacity and resource constraints at national, district and local levels, legal pluralism and diverging interests of the actors in the water sector were not amenable to reaching the ambitious objectives of the programme. There was a pervasive lack of knowledge bases for informed decision-taking and of coordination among aid agencies. While water supply infrastructure was in high demand, the inability or unwillingness of communities to pay their share of capital cost contributions was a cross-cutting issue of major concern. Where improved systems had been established sustainability was often doubtful because of insufficient levels of water tariffs and, concerning small urban supply systems, by ineffective management, operation and maintenance. Utilisation of the improved sources once established or rehabilitated turned out to be limited, which was due to both environmental (water quality and quantity) and socio-political factors involving issues of acceptance, 'elite capture' and equity. Ongoing reforms, particularly in the framework of the Ghana Poverty Reduction Strategy, were aiming to resolve some of the problems. The peculiar logic of the world of development aid constituted differing interests and institutional constraints among the actors, which are ultimately considered to be at the root of the difficulties observed.
urn:nbn:de:0202-2008091141
Keywords: 360